FACTORS ASSOCIATED WITH STRESS AND COPING AT 5 AND 10 YEARS AFTER HEART TRANSPLANTATION - Grady, Kathleen L. (2013)
BACKGROUND: Heart transplant-related stressors and coping are related to poor outcomes early after transplant. The purposes of our study were to (1) identify the most frequent and bothersome stressors and most used and effective coping strategies, and (2) compare the most frequent and bothersome stresses and most used and effective coping styles between patients at 5 and 10 years after heart transplantation. We also examined differences in coping styles by patient characteristics, and factors associated with frequency and intensity of stress at both 5 and 10 years after heart transplantation. METHODS: This report is a secondary analysis of data from a prospective, multi-site study of quality of life outcomes. Data are from 199 and 98 patients at 5 and 10 years after transplant, respectively. Patients completed the Heart Transplant Stressor Scale and Jalowiec Coping Scale. Statistical analyses included frequencies, measures of central tendency, t-tests, Chi-square and generalized linear models. RESULTS: At 5 and 10 years after heart transplantation, the most bothersome stressors were regarding work, school, and financial issues. Patients who were 10 years post transplant reported less stress, similar stress intensity, and less use and perceived effectiveness of negative coping than patients who were 5 years post transplant. Long-term after transplant, demographic characteristics, psychological problems, negative coping, and clinical factors were related to stress frequency and/or intensity. CONCLUSIONS: Heart transplant-related stress occurs long-term after surgery. Types of transplant-related stress and factors related to stress confirm the importance of ongoing psychological and clinical support after heart transplantation.